Craig & George, Force and statecraft - Diplomatic problems of our time - Votaw, John (Teaching History: A Journal of Methods, 1991)
The first edition [1983] of this practical book of international relations evolved from the authors' course on contemporary problems of foreign policy at Stanford University. Case studies by students, some of whom later taught history at the U.S. Military Academy, contribute to the book's intended purpose of presenting working hypotheses about problems of American foreign policy in the nineteenth and twentieth centuries.